Gambaran Perilaku Lansia Pada Masa Menopause di Posyandu Lansia Desa Tambak Baru Ilir Martapura - Siska Dhewi (Universitas Faletehan, 2019)
Elderly is a natural decline in the ability of organs, functions and systems of the body. The aging process appears at the age of 45 years and causes problems at the age of 60 years. For women to grow old, it becomes a frightening specter. This concern begins with the thought that he will be sick and not beautiful anymore. The type of research used is qualitative, namely research that produces descriptive data in the form of written or oral words from people and behavior that is observed and directed at the background and the individual as a whole. The sampling technique used is purposive sampling, namely the technique of determining the sample to find data or information according to the criteria and objectives of the researcher. Research subjects 4 of 27 elderly women, all had experienced menopause and had husbands. Research subjects aged 56 - 63 years, living with their husbands and children and grandchildren. The level of knowledge of the elderly about menopause and reproductive health is still quite good, although most do not know the signs of symptoms and changes that occur at menopause because they feel it is natural. The attitude of the elderly at menopause almost all feel ready to face and accept, because they think it's normal. They only pay less attention to how to maintain reproductive health at menopause. The practice of the elderly during menopause is quite active routinely visiting the Posyandu every month, and says that they rarely have sexual relations.